Religious façade of 'the Chinese nation' in China's school curriculum. Issue 2 (4th March 2022) - Zhao, Zhenzhou
ABSTRACT: The shaping of people's identities as members of the Chinese nation is crucial to China's nationalist discourse at school. What kind of image of the Chinese nation does the state intend to transmit to its new generation of citizens? Does the constitutional separation of religion and education prescribe a secular image for the collective identity of the Chinese nation? This study explores how the interpretation of religion is manufactured during the discourse of constructing the nation in Chinese school textbooks. The findings reveal that different religious traditions are assigned strikingly different roles in the national curriculum's interpretation of the Chinese nation as a construct and the distinction between China and the external world. The integration of religious narratives and the agenda of shaping the national cultural identity of Chinese students reveal the changing role of religion in contemporary Chinese society.